EFEKTIVITAS PERMAINAN PUZZLE TANGKAI UNTUK MENGENALKAN BANGUN DATAR SEDERHANA BAGI ANAK TUNARUNGU KELAS II B - Almira Silvia, Martias, Z, Yarmis Hasan (Universitas Negeri Padang, 2013)
This research begins with the reality that found in SDLB. No. 20 Nan Balimo Solok city, a deaf child who still don’t know introduce the simple build flatks. This research aims to introduce a simple build flatks for deaf child. The hypothesis in research is the usage puzzle stalk games effective to introduce a simple build flatks for deaf child class II. This research used approach experimental in the form of Single Subject Research (SSR) using A-B-A design. Research carried out consistently with the test action by assessing how much the child can answer to the question with time faster from ability before child by observation direct. Analysis data this research is data visual graph. Conditions (A1) the ability of the child to the value of 20% and the time spent in 25 minutes, and increased to 100% with time 15 minutes in the intervention condition (B) by the puzzle stalk games, after a given time interval at baseline 2 (A2) without using a media value of 100% time used a 15 minutes. With thus the proposed hypothesis can be accepted, so the by puzzle stalk games can improve the ability to introduce simple build flatks for deaf child in SDLB. No. 20 Nan Balimo Solok city.